Effect of Acute Sodium Bicarbonate Intake on Sprint-Intermittent Performance and Blood Biochemical Responses in Well-Trained Sprinters - Mohammad Fayiz AbuMoh'd; Walid Alsababha; Yazan Haddad; Ghaid Obeidat; Yaser Telfah (Montenegrin Sports Academy, 2021)
The present study was designed to determine the acute effect of sodium bicarbonate (NaHCO3) on the number of sprint repetitions during sprint high-intensity intermittent testing. In addition, blood biochemical (pH, HCO3-, and lactate) responses measured in three occasions were investigated. Thirteen male well-trained sprinters (24.65±3.44 yrs) performed two consecutive trials (7 days apart). Athletes were assigned randomly either to ingest a single dose of NaHCO3 (0.3 g/kg) 1 h prior to exercise or placebo using a double-blind crossover design. The intermittent sprint test consisted of 60 s treadmill sprints (90% of maximal work done) and 30-s recovery repeated intermittently until volitional exhaustion. Blood samples were collected from all athletes before exercise, after 1 h of dose intake, and after exercise in each trial. Paired sample t-testing showed that athletes complete significantly more sprint repetitions (p=0.036) during the intermittent sprint test with NaHCO3 (6.846±3.114) than with the placebo (5.538±3.872). Data also revealed no differences between trials in all blood responses at pre-exercise. After 1 h of dose consumption, however, blood pH and HCO3- were higher with NaHCO3 than with placebo (p<0.05), but no differences were noted in lactate between trials (p>0.05). After completion of the test, all blood responses were significantly higher with NaHCO3 than with placebo (p<0.05). In conclusion, intake of 0.3 g/kg of NaHCO3 1 h prior to treadmill sprint-intermittent performance increased sprint repetitions in well-trained sprinters, probably due to activated glycolysis caused by intracellular protons efflux into the blood.